2013
DOI: 10.1117/1.jbo.18.4.046010
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography for assessment of microbicide safety in a small animal model

Abstract: Sensitive imaging techniques for small animals are needed to assess drug toxicity in preclinical studies. Optical coherence tomography (OCT) provides a noninvasive tool for high-resolution, depth-resolved visualization of drug-induced changes in tissue morphology. In a mouse model, we utilize OCT to assess vaginal tissue integrity following the application of topical microbicides (drugs used to prevent infection). Mice are challenged with herpes simplex virus-2 (HSV-2) to determine the correlation of tissue da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…3,6 Vincent et al 4 detected N-9-induced vaginal epithelial thinning and injury in human subjects from OCT B-scans, which could not otherwise be identified by conventional colposcopy. More recently, Bell et al 16 applied fiber-based endoscopic OCT to safe assessment of vaginal microbicide, which involved measurement of epithelial and stromal thicknesses of mouse vagina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6 Vincent et al 4 detected N-9-induced vaginal epithelial thinning and injury in human subjects from OCT B-scans, which could not otherwise be identified by conventional colposcopy. More recently, Bell et al 16 applied fiber-based endoscopic OCT to safe assessment of vaginal microbicide, which involved measurement of epithelial and stromal thicknesses of mouse vagina.…”
Section: Introductionmentioning
confidence: 99%
“…First, the imaging systems only achieved moderate resolution. Both axial and lateral resolutions were tens of micrometers, 3,4,6,16 which may not be ideal to resolve the mucosal and epithelial interface clearly and to evaluate epithelial integrity. Second, the imaging systems only provided cross-sectional B-scans of vaginal epithelial morphology.…”
Section: Introductionmentioning
confidence: 99%
“…5) indicated that this protective layer was affected. An interesting finding was that injury could be induced using even the very low concentration of 0.01%, a dose several times smaller than found in many products and one which is much smaller than doses found to result in partial denuding of the superficial vaginal epithelium (33)(34)(35). This is likely due to the fact the rectal epithelium only comprises a single layer of columnar cells.…”
Section: Discussionmentioning
confidence: 86%
“…The effects of BZK on epithelium are known (32)(33)(34)(35). Since BZK results in superficial denuding of epithelium, it provided a means to induce structural injury similar to that expected with either mechanical or chemical injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation